Nilai Kearifan Lokal dalam Tradisi Bebantai Kerbau dalam Menyambut Bulan Suci Ramadhan di kabupaten Merangin - Giohilda Sijabat; Ahmad Hariandi; Dea Elizabeth Ginting Suka; Miranda Sari Tobing; Mellani Aprilia (Al-Mashlahah: Jurnal Hukum Islam dan Pranata Sosial, 2022)
This article aims to describe the traditional bantai tradition as local wisdom to welcome the month of Ramadan for the Merangin Jambi community. This research was conducted for study, understand and analyze the phenomenon of the people of Merangin Regency, especially in the traditional bantai tradition related to religion. This article was written objectively from the results of participant observations, interviews and literature studies conducted on the community Merangin. Traditional slaughter is a tradition of slaughtering livestock such as cows and buffalo which aims to welcome the month of Ramadan and is carried out a few days before the month of Ramadan. The values contained in the traditional bantai tradition include social values, religious values and local cultural values. By getting to know the traditional slaughtering tradition of the Merangin people, it can make the public know about the traditions that exist in Jambi Province.